Gravitational radiation, collapsed objects and exact solutions : proceedings of the Einstein Centenary Summer School, held in Perth, Australia, January 1979 - Einstein Centenary Summer School (1979 : Perth, Australia); Edwards, C. (Berlin : Springer-Verlag, 1980)
40